2020
DOI: 10.1101/2020.05.15.098251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optical control of ERK and AKT signaling promotes axon regeneration and functional recovery of PNS and CNS inDrosophila

Abstract: 15Neuroregeneration is a dynamic process synergizing the functional outcomes of multiple 16 signaling circuits. Channelrhodopsin-based optogenetics shows feasibility of stimulating neural 17 repair but does not pin down specific signaling cascades. Here, we utilized optogenetic systems, 18 optoRaf and optoAKT, to delineate the contribution of the ERK and AKT signaling pathways to 19 neuroregeneration in live Drosophila larvae. We showed that optoRaf or optoAKT activation not 20 only enhanced axon regeneration … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…The kinase activity is required for F-iTrkB transphosphorylation at Tyr515, causing F-iTrkB to interact with the adaptor proteins Shc and GRB2. This interaction is known to induce multiple complex formations with Ras and PI3K, followed by activation of the Ras-ERK and PI3K-AKT signaling, both of which play crucial roles in neuroprotection and axon regeneration (23)(24)(25)(26)(27). Indeed, both F-iTrkB and F-iTrkA successfully activated these signals in vitro, and optic nerve regeneration was observed in vivo with intraocular injection of AAV-F-iTrkB and AAV-F-iTrkA.…”
Section: Discussionmentioning
confidence: 99%
“…The kinase activity is required for F-iTrkB transphosphorylation at Tyr515, causing F-iTrkB to interact with the adaptor proteins Shc and GRB2. This interaction is known to induce multiple complex formations with Ras and PI3K, followed by activation of the Ras-ERK and PI3K-AKT signaling, both of which play crucial roles in neuroprotection and axon regeneration (23)(24)(25)(26)(27). Indeed, both F-iTrkB and F-iTrkA successfully activated these signals in vitro, and optic nerve regeneration was observed in vivo with intraocular injection of AAV-F-iTrkB and AAV-F-iTrkA.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus plausible that growth factors, neurotransmitters, and peptides can regulate axon regeneration through regulation of Ras activity. Among the many Ras targets, the canonical MAPK pathway has been shown to regulate axon regeneration, as activation of this pathway promotes axon regeneration in both mammals and flies (Hollis et al, 2009;O'Donovan et al, 2014;Perlson et al, 2005;Wang et al, 2020), and activated ERK has been found to transport retrogradely from the injury site to the cell body (Perlson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate how Ca 2+ spikes determine axon regeneration, we focused on Ras GTPase as a potential downstream effector based on the findings that intracellular Ca 2+ activates Ras and that mitogen-activated protein kinase (MAPK) pathways regulate axon regeneration in both mammals and flies (Hollis et al, 2009;O'Donovan et al, 2014;Perlson et al, 2005;Rosen et al, 1994;Wang et al, 2020). We found that reducing Ras activity in C4da neurons, by expressing the Drosophila or mouse version of dominant negative Ras (Ras DN ), significantly impaired axon regeneration (Figure 6A-6B).…”
Section: Neuronal Type-specific Ras Activity Determines Axon Regenera...mentioning
confidence: 99%
“…Egfr and Heartless in glia both signal through ERK to promote different outcomes: inducing differentiation of the photoreceptor target field and ensheathment of photoreceptor axons, respectively (Fernandes et al, 2017; Franzdóttir et al, 2009). Recent advances in the development of optogenetic tools to manipulate ERK signalling in flies have enabled a fine dissection of the temporal requirements for ERK activity during development, and refined our understanding of the signalling dynamics in cell fate decisions (Bunnag et al, 2020; Johnson and Toettcher, 2019; Johnson et al, 2017; Patel et al, 2019; Wang et al, 2020; Yadav et al, 2021). Thus, the ability to monitor ERK activity dynamics in Drosophila, in combination with the tools to manipulate it, would provide an unparalleled understanding of how temporal signalling dynamics regulate fate decisions.…”
Section: Introductionmentioning
confidence: 99%